Efficient Fault Detection in Power Transmission: A Review of Three-Phase Line Fault Detection with Hybrid Energy using MATLAB - Sagar Chaudhari; Varad Gurav; Chinmay Upasani; Suraj Ghule; Sharad S. Patil (International Journal of Electrical Power and Machine Systems, 2024)
In urban regions, the density of power demand has significantly increased recently. Large-scale subterranean power cable installations are beginning to take the place of overhead transmission lines everywhere in the world because of environmental concerns in highly populated areas. The present project's primary objective is to use MATLAB to create a simulation model that includes 3ph symmetrical and unsymmetrical defects. Some have proven to be effective in detecting errors while the system is operating. With a few exceptions there hasn't been much research on fault location methods for line-selection devices in industrial systems that aren't grounded, including those running at 35 kV and lower.This document describes how to handle MATLAB programming, which is used to create gearbox line models and reenact various problems using tool compartments. Numerous types of defects have been analysed, and the results show up in the simulation output. Examples of these include control, voltage, and current, as well as the positive, negative, and zero grouping parts of the voltage and current output. Consequently, utility is being requested to improve the precision of fault location and fault section discrimination in integrated transmission lines.
Keywords: 3 phase transmission line; Fault detection; matlab simulation; solar and wind energy